Cerebral Venous Sinus Thrombosis in Closed Head Injury: Systematic Review and Meta-analysis. (April 2022) - Alghamdi, Saad R.; Cho, Anna; Lam, Jack; Al-Saadi, Tariq
Highlights: Cerebral venous sinus thrombosis (CVST) is a rare cerebrovascular condition, causing 0.5% of all strokes. Due to the rarity of occurrence and nonspecific varieties of symptoms, such as headache, papilledema, or focal neurological deficits, the diagnosis of CVST might be often missed. The majority of cases presented with loss of consciousness or decreased GCS (41%), followed by headache (26%), scalp abrasions/lacerations (21%), paralysis (18%), visual disturbance (18%), nystagmus (15%), and agitation (15%). The current study showed that the non-surgical outcomes were better than the surgical outcomes. Abstract: Background: Cerebral venous sinus thrombosis (CSVT) is a rare condition, causing 0.5% of all strokes only, several mechanisms might be involved in forming the thrombosis, including closed head injury. Methods: Systematic review was done by using the following databases: PubMed, Google Scholar, Microsoft Academic, Clinical Trials, Cochrane Library, and Web of Science. Results: 25 articles met our criteria out of 152 articles, average and standard deviation of the age was 38.2 ± 16.8 years with an age range of 18–82. The majority of cases presented with loss of consciousness or decreased GCS (41%), followed by headache (26%), scalp abrasions/lacerations (21%), paralysis (18%), visual disturbance (18%), nystagmus (15%), and agitation (15%). The most commonly used diagnostic method was angiography. Thrombosis was the most frequently reported radiological finding among all the cases (26/34, 76%). Comparisons of outcomes between patients who underwent surgical intervention and those who did not undergo surgery revealed a significant difference in outcome favoring non-surgical treatment (p < 0.005, odds ratio (OR) 0.04, (95% CI) 0.003 – 0.30). Conclusion: Non-surgical outcomes were better than the surgical outcomes. However, no significant difference was seen comparing anti-coagulation versus conservative management (supportive without anticoagulation), single versus multi-sinuses (≥2 sinuses) involvement, and between any of the sinuses involved.